A comparative study of the electronic spectra, fluorescence quantum yields, cyclic voltammograms and theoretical calculations of phenanthrene-type benzodifurans. Issue 29 (21st July 2016) - Hayashi, Naoto; Saito, Yoko; Zhou, Xiaoxi; Yoshino, Junro; Higuchi, Hiroyuki; Mutai, Toshiki
Abstract: Three isomeric difuran analogs of phenanthrene, including benzo[1, 2- b ;6, 5- b ′]difuran (3O ), benzo[1, 2- b ;4, 3- b ′]difuran (4O ) and benzo[1, 2- b ;3, 4- b ′]difuran (5O ) have prepared and their properties investigated systematically. Compared with benzo[1, 2- b ;4, 5- b ′]difuran (1O ) and benzo[1, 2- b ;5, 4- b ′]difuran (2O ), there were pronounced differences in the fluorescence quantum yields of3O–5O . Consideration of the absorption and fluorescence spectra, cyclic voltammograms and B3LYP/6-31G(d, p) calculations revealed that4O had the highest electron-donating/accepting characteristics of all of the compounds prepared in this study. The lower electron-donating/accepting properties of5O were attributed to the shorter chain length of it π-conjugated system. The unexpectedly high electron-donating and low electron-accepting properties of3O were attributed to changes in the radical cationic and anionic states, respectively. The energy levels of the highest occupied and lowest unoccupied molecular orbitals of the thiophene and selenophene analogs of3O–5O have also been calculated, and their relative energies explained in a similar manner. Graphical abstract: